Reassuring the Reluctant Warriors : U.S. Civil-Military Relations and Multilateral Intervention - Recchia, Stefano, 1978- (Book collections on Project MUSE., 2015)
Why did American leaders work hard to secure multilateral approval from the United Nations or NATO for military interventions in Haiti, Bosnia, and Kosovo, while making only limited efforts to gain such approval for the 2003 Iraq War? This book illuminates little-known aspects of U.S. decision making in the run-up to those interventions.